2012
DOI: 10.1029/2011jb008897
|View full text |Cite
|
Sign up to set email alerts
|

Auto‐acoustic compaction in steady shear flows: Experimental evidence for suppression of shear dilatancy by internal acoustic vibration

Abstract: [1] Granular shear flows are intrinsic to many geophysical processes, ranging from landslides and debris flows to earthquake rupture on gouge-filled faults. The rheology of a granular flow depends strongly on the boundary conditions and shear rate. Earthquake rupture involves a transition from quasi-static to rapid shear rates. Understanding the processes controlling the transitional rheology is potentially crucial for understanding the rupture process and the coseismic strength of faults. Here we explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 56 publications
3
64
0
Order By: Relevance
“…The quantity ρ should be a function of the vibrational frequency and amplitude; past studies [14,15,41] suggest that ρ is proportional to the vibrational amplitude, and the square of the frequency. However, the detailed dependence is unimportant for the purposes of this paper which, as in the van der Elst et al experiments [31], focuses on one single amplitude and frequency, unless otherwise specified.…”
Section: Nonequilibrium Thermodynamics Of Driven Granular Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity ρ should be a function of the vibrational frequency and amplitude; past studies [14,15,41] suggest that ρ is proportional to the vibrational amplitude, and the square of the frequency. However, the detailed dependence is unimportant for the purposes of this paper which, as in the van der Elst et al experiments [31], focuses on one single amplitude and frequency, unless otherwise specified.…”
Section: Nonequilibrium Thermodynamics Of Driven Granular Mediamentioning
confidence: 99%
“…The basic idea is that the coupling K between the configurational and kinetic-vibrational subsystems consists of additive contributions of the fluctuations Γ induced by shearing, ξ induced by interparticle friction, and ρ induced by external vibrations (when switched on). In our analysis [30] of a series of experiments by van der Elst et al [31], these are referred to as mechanical, frictional, and vibrational noise strengths. The effect of ξ and ρ on granular rheology is clearly illustrated there.…”
Section: Introductionmentioning
confidence: 99%
“…9, 10, 11 therein). Recently, carrying out an experiment of granular shear flow, Van Der Elst et al (2012) also discovered a "strain-localization-zone contracting" phenomenon that is caused by a granular rheology, not by the "strain-softening" behaviour. In earlier research (Mül-haus and Vardoulakis 1987), the strain localization zone observed for sand had a thickness on the order of tens times the mean particle size, the thickness probably ranging between millimeters and centimeters.…”
Section: Shear Zone Introductionmentioning
confidence: 99%
“…In this way seismic failure is promoted. To investigate this scenario, experimental studies [1,2,6,7] have demonstrated that acoustic perturbations modify granular rheology and lead to auto-acoustic compaction [7]. Recently the AF scenario has been explored in 3D molecular dynamics simulations [23] which have shown that weak external perturbations, at the frequency ω AF , even if increasing the confining pressure or reducing the applied shear, induce slip instabilities.…”
mentioning
confidence: 99%
“…Confined granular materials under shear display the typical stick-slip dynamics observed in real fault systems. In the last years this dynamics has been deeply investigated in several experimental settings as well as by means of molecular dynamics simulations [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These studies mostly focus on two central questions: i) Why the stress responsible for seismic failure is usually orders of magnitude smaller than the value expected on the basis of rock fracture mechanics?…”
mentioning
confidence: 99%